2015
DOI: 10.1007/s00404-015-3650-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the IGF system and proliferation in human endometrial stromal cells by metformin: a dose-dependent effect

Abstract: We were able to demonstrate for the first time a dose-dependent local effect of metformin within hESCs. Metformin might therefore influence locally the endometrial proliferation and maturation, and could open up new treatment options for gynecological diseases by vaginal application of metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…Since, however, stromal maturation was not affected, it is not known if this delay in only one aspect of endometrial maturation can have an impact on embryo implantation. In vitro experiments have demonstrated that metformin diminishes decidualization and stromal cell proliferation in human endometrium in a dose-dependent manner [38]. However, extrapolating the in-vitro data into clinical reality is a challenge but requires confirmation via clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Since, however, stromal maturation was not affected, it is not known if this delay in only one aspect of endometrial maturation can have an impact on embryo implantation. In vitro experiments have demonstrated that metformin diminishes decidualization and stromal cell proliferation in human endometrium in a dose-dependent manner [38]. However, extrapolating the in-vitro data into clinical reality is a challenge but requires confirmation via clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Это предположение на-ходит свое подтверждение в исследовании in vitro на клеточной линии стромальных клеток эндометрия, в котором были показаны дозоза-висимые эффекты метформина. Применение препарата в концентрации 10 -4 М вызывало децидуализацию клеток, увеличение концен-трации до 10 -3 М сопровождалось подавлением клеточной пролиферации [15].…”
unclassified